Minimum income support systems as elements of crisis resilience in Europe - Werner Eichhorst; Annabelle Krause-Pilatus; Paul Marx; Mathias Dolls; Max Lay (University of Essex, Institute for Social and Economic Research (ISER), 2023)
This paper studies the role and performance of social policies in different European welfare states regarding minimum income protection during periods of crisis. To achieve this goal, the paper expands its analytical focus to include other tiers of social protection, in particular upstream systems such as unemployment insurance, job retention and employment protection. A mixed-method approach is used combining quantitative and qualitative research, such as descriptive and multivariate quantitative analyses, microsimulation methods and in-depth case studies. We find consistent differences in terms of crisis resilience across countries and welfare state types. In general, Nordic and Continental European countries with strong upstream systems and minimum income support show better outcomes in socio-economic outcomes such as poverty and exclusion risks. However, labour market integration shows some dualisms in Continental Europe. The study shows that MIS holds particular importance if there are gaps in upstream systems or cases of severe and lasting crises.
Keywords: J64; J65; J68; 330; minimum income support; crisis resilience; unemployment insurance; job retention; welfare states